Barriers and opportunities for the mental health of LGBT older adults and older people living with HIV: a systematic literature review. (24th August 2022) - Marshall, Austin; Cahill, Sean
Abstract: Objective: LGBT older adults and older people living with HIV (PLWH) experience a disproportionate burden of behavioral health conditions compared to their heterosexual, cisgender, and HIV-negative peers. This study intends to systematically review the literature regarding accessing mental health care among LGBT older adults and older PLWH. Methods: This study was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Statement framework. Three databases were searched using Boolean search strings, and inclusion/exclusion criteria were developed and applied to the search outcomes to appropriately narrow results. Article quality and evidence of bias were evaluated using the National Heart, Lung, and Blood Institute (NHLBI) quality-assessment tool, and the Critical Appraisal Skills Program (CASP) assessment tool, two instruments used to help reviewers in assessing for internal validity of studies. Two independent researchers coded the articles for themes, and consensus was reached on theme grouping through an iterative process. Results: Out of 2, 031 articles initially screened, 28 met all inclusion criteria and advanced to final analysis. Several key themes emerged, including a lack of provider competency in caring for LGBT patients, lower rates of insurance coverage, greater mental health burden, social and structural determinants of health, policy solutions, and technology and health literacy. Conclusion: There were several domains identified in the literature as barriers to accessing mental healthcare, as well as opportunities to better attend to the mental health needs of these populations. Provider training, implementing health technology solutions, and enacting public policy changes could improve mental health outcomes.